2018
DOI: 10.1021/acsomega.8b00179
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of TMPA Derivatives through Sequential Ir(III)-Catalyzed C–H Alkylation and Their Antidiabetic Evaluation

Abstract: The synthesis and antidiabetic evaluation of ethyl 2-[2,3,4-trimethoxy-6-(1-octanoyl)phenyl]acetate (TMPA) and its structural analogs are described. The construction of TMPA derivatives has been successfully achieved in only two steps, which involve the iridium(III)-catalyzed α-alkylation of acetophenones with alcohols and the ketone-directed iridium(III)- or rhodium(III)-catalyzed redox-neutral C–H alkylation of α-alkylated acetophenones using Meldrum’s diazo compounds. This synthetic protocol efficiently pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…294 With dimethyl (1-diazo-2oxopropyl)-phosphonate as the carbene source compound 3indolylphosphonates were accessed in 59-75% yields. Other directing groups such as pyridyl, 295 ketone, 296 phosphine oxide, 297 and pyrazolyl 298 were also applied in iridiumcatalyzed intermolecular aryl C(sp 2 )-H functionalization by carbene insertion with diazo compounds. Under Ir(III) catalysis 2-(arylamino)pyridines (191) reacted with acceptor/acceptor diazo compound 260 in the presence of LiOAc in CF 3 CH 2 OH (TFE) to afford oxindole derivatives 261 in up to 72% yields (eqn ( 64)).…”
Section: Carbene Insertion To Aryl C(sp 2 )-H Bonds Of Nonactivated A...mentioning
confidence: 99%
See 1 more Smart Citation
“…294 With dimethyl (1-diazo-2oxopropyl)-phosphonate as the carbene source compound 3indolylphosphonates were accessed in 59-75% yields. Other directing groups such as pyridyl, 295 ketone, 296 phosphine oxide, 297 and pyrazolyl 298 were also applied in iridiumcatalyzed intermolecular aryl C(sp 2 )-H functionalization by carbene insertion with diazo compounds. Under Ir(III) catalysis 2-(arylamino)pyridines (191) reacted with acceptor/acceptor diazo compound 260 in the presence of LiOAc in CF 3 CH 2 OH (TFE) to afford oxindole derivatives 261 in up to 72% yields (eqn ( 64)).…”
Section: Carbene Insertion To Aryl C(sp 2 )-H Bonds Of Nonactivated A...mentioning
confidence: 99%
“…Aryl alkyl ketones 263 reacted with 2diazotized Meldrum's acid (173) under the conditions similar to those shown in Scheme 80 293 to produce the alkylated ketone products 264 in moderate to excellent yields without occurrence of carbene insertion to the alkyl C(sp 3 )-H bonds (eqn (66)). 296 In the presence of 2,4,6-trimethylbenzoic acid (TMBzOH) arylphosphine oxides 265 underwent Ir(III)-catalyzed ortho-C-H functionalization by carbene insertion with 2,4-dichloro-6diazocyclohexa-2,4-dienone (266), giving the corresponding biphenyl-based arylphosphine oxide products 267 in 42-88% yields (eqn ( 67)). 297 The analogs of 266 and 1diazonaphthoquinones were also applied for the synthesis of multi-functionalized arylphosphine oxides, which are potentially useful MOP-type ligand precursors.…”
Section: Carbene Insertion To Aryl C(sp 2 )-H Bonds Of Nonactivated A...mentioning
confidence: 99%
“…Plant secondary metabolites are a diverse range of biologically active molecules having multiple pharmacological actions like antimicrobial, stimulant, analgesic, anthelmintic, anticoagulant, antiacne, and antioxidant, among others (Debnath et al, 2012;Bhakta, 2012, 2013;Dey et al, 2012bDey et al, , 2014Karuna et al, 2018aKaruna et al, , 2018bKundu et al, 2019). Different synthetic compounds show potential biological activity in vitro as well as in vivo ( Jeon et al, 2017;Jeong et al, 2017a, b;Kim et al, 2018;Lee et al, 2018Lee et al, , 2019Richa et al, 2019;Tae et al, 2018), and various formulations of existing drugs are also developed to increase the safety profile (Gorain et al, 2014;Karmakar et al, 2015;Maity et al, 2016). In spite of this technological development, humans from almost every culture are efficiently employing the plant-derived compounds for the anticipation and management of multiple health disorders for many centuries (Dey et al, 2012a, c).…”
Section: The Biological Activity Of Alkaloidsmentioning
confidence: 99%
“…With this methodology, the group also found that increasing the length of α ‐alkyl chain on acetophenone and the position of aromatic OMe substituents play an important role for the AMPK activation and antidiabetic effect (Scheme 25). [37] …”
Section: C−h Alkylation With Carbene Precursorsmentioning
confidence: 99%